Optimizing Polymyxin Combinations Against Resistant Gram-Negative Bacteria. Issue 4 (December 2015) - Bergen, Phillip; Bulman, Zackery; Landersdorfer, Cornelia; Smith, Nicholas; Lenhard, Justin; Bulitta, Jürgen; Nation, Roger; Li, Jian; Tsuji, Brian
Abstract Polymyxin combination therapy is increasingly used clinically. However, systematic investigations of such combinations are a relatively recent phenomenon. The emerging pharmacodynamic (PD) and pharmacokinetic (PK) data on CMS/colistin and polymyxin B suggest that caution is required with monotherapy. Given this situation, polymyxin combination therapy has been suggested as a possible way to increase bacterial killing and reduce the development of resistance. Considerable in vitro data have been generated in support of this view, particularly recent studies utilizing dynamic models. However, most existing animal data are of poor quality with major shortcomings in study design, while clinical data are generally limited to retrospective analysis and small, low-power, prospective studies. This article provides an overview of clinical and preclinical investigations of CMS/colistin and polymyxin B combination therapy.